Characterization and Antioxidant Potential Albumin Protein of Canna striata Fish to Rattus Novergicus Induced by Isoniazid Toxic Dose - Indahsari, Noer Kumala (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: The Canna Striata fish is a potent source of albumin as an antioxidant. Albumin is a protein capable of binding to free radicals in plasma and has 17 disulfide bonds linking sulfur-containing amino acids. The existence of thiol group bonds in albumin extract of Canna Striata fish is possible to bind to diphenylphycril hydrazyl (DPPH), causing the antioxidant capacity of Canna Striata fish extract to be high. The accumulation of free radicals produced by the administration of antituberculosis drugs from the results of isoniazid metabolism can cause hepatic necrosis. So it requires antioxidants that can reduce free radical levels, which in this study was tested in white rats induced with isoniazid and then treated with albumin protein extract Canna Striata fish. This research method is the first experimental method done is the characterization of albumin protein extract Canna Striata fish with temperature 25ËC and 40ËC by Sodium Dodecyl Sulfate Polyacrilamide Gel Electrophoresis (SDS-PAGE). Then the antioxidant level was tested by measuring the levels of Malondialdehyde (MDA) after 2 last week treatment period in 5 groups of white rats are positive control group, negative control group and 3 treatment groups induced Isoniazid toxic dose are 37.8 mg accompanied by giving of albumin protein extract Canna Striata fish with content of 20ml/kg, 40 ml/kg and 60 ml/kg. The result of this study showed that there were ten albumin protein profiles with size 15,41 kDa, 19,74 kDa 28,6 kDa, 38,87 kDa, 46,08 kDa, 72,45 kDa, 94,42 kDa , 120.82 kDa, 142.80 kDa, and 155.97 kDa. Based on One Way ANOVA and Post Hoc Tukey statistic test, it were found that there was the significant influence and differentiation of Malondialdehyde (MDA) level on giving of albuminÂ protein extract in white rats induced by Isoniazid with p-value 0,002. The most effective decrease in MDA levels is high levels of albumin protein extract of 60 ml/kg.Â Keywords: Albumin Protein Extract of Canna Striata, Malondialdehyde, Isoniazid